Implementasi Program Sistem Informasi Kinerja Pegawai Kabupaten Probolinggo (SIKePPo) - Husni Mubaraq; Binti Nasikhatul Ummatin (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
To improve and supervise the performance of the State Civil Apparatus (ASN) within the Probolinggo Regency Government, the local Regional Personnel Agency (BKD) made a breakthrough with a reporting application. Performance reporting through an application called SIKePPo or the Probolinggo Regency Government Employee Performance Information System application. The program implementation by the Regional Personnel Agency (BKD) of Probolinggo Regency seeks to improve personnel management and administration quickly, precisely and accurately. Although this program has been implemented well, it has not yet achieved optimal results. This study seeks to analyze the effectiveness of the implementation of program policies in the BKD of Probolinggo Regency. The two problems studied are: (1) the effectiveness of the implementation of the web-based SIKePPo program at the Probolinggo District BKD, and (2) the factors that influence the implementation of the SIKePPo program. The purpose of the study was to determine the effectiveness of the implementation of the web-based SIKePPo program at the Probolinggo District BKD and the factors that hindered the implementation of the web-based SIKePPo program at the Probolinggo District BKD. The approach used in this research is descriptive qualitative method with the application of Edwards III theory and Bambang Sunggono theory. Data was collected by means of observation, in-depth interviews, and documentation. The selection of informants used purposive sampling technique, and qualitative data analysis was inductive. The results showed that the implementation of the web-based SIKePPo program at the BKD of Probolinggo Regency was running quite well in accordance with the four elements that determine policy implementation, namely communication, resources, disposition, and bureaucratic structure. The factors that become obstacles in the implementation of the web-based SIKePPo program at the Probolinggo District BKD are related to policy content, HR support, infrastructure and communication facilities.